2013
DOI: 10.1113/jphysiol.2013.253203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leucine and its metabolite β‐hydroxy‐β‐methylbutyrate on human skeletal muscle protein metabolism

Abstract: Key points• The branched-chain amino acid (BCAA) leucine acts as both a 'trigger' for the initiation of protein synthesis, and as a substrate for newly synthesized protein.• As a BCAA, leucine can be metabolized within skeletal muscle, leaving open the possibility that leucine metabolites might possess anabolic properties.• One metabolite in particular, β-hydroxy-β-methylbutyrate (HMB), has shown positive effects on lean body mass and strength following exercise, and in disease-related muscle wasting, yet its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
421
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(449 citation statements)
references
References 38 publications
19
421
2
7
Order By: Relevance
“…This was slightly surprising since mTORC1 activation is associated with inhibition of autophagy (Sandri, 2013), and there is evidence that amino acid ingestion can also prevent elevations in MuRF‐1 ( Trim63 ) and MAFbx ( Fbxo32 ) expression at rest and following exercise (Borgenvik, Apro, & Blomstrand, 2012; Herningtyas et al, 2008). Our in vitro data support in vivo human data reporting no alterations in proteolytic gene expression following ingestion of leucine or its metabolite β‐Hydroxy‐β‐methylbutyrate in healthy young men (Wilkinson et al, 2013), although, since we measured changes in mRNA expression, we cannot discount the possibility that differences may have been observed at an earlier time point.…”
Section: Discussionsupporting
confidence: 82%
“…This was slightly surprising since mTORC1 activation is associated with inhibition of autophagy (Sandri, 2013), and there is evidence that amino acid ingestion can also prevent elevations in MuRF‐1 ( Trim63 ) and MAFbx ( Fbxo32 ) expression at rest and following exercise (Borgenvik, Apro, & Blomstrand, 2012; Herningtyas et al, 2008). Our in vitro data support in vivo human data reporting no alterations in proteolytic gene expression following ingestion of leucine or its metabolite β‐Hydroxy‐β‐methylbutyrate in healthy young men (Wilkinson et al, 2013), although, since we measured changes in mRNA expression, we cannot discount the possibility that differences may have been observed at an earlier time point.…”
Section: Discussionsupporting
confidence: 82%
“…Leucine concentrations in blood plasma and muscles were not altered after oral HMB consumption in humans 12. We suppose that the difference between the results of animal and human studies is due to the dose, duration, and route of HMB administration.…”
Section: Effects Of Hmbmentioning
confidence: 73%
“…The HMB stimulates protein synthesis via mTOR, a protein kinase that has a central role in controlling mRNA translation efficiency 12. Recently, Girón et al .…”
Section: Effects Of Hmbmentioning
confidence: 99%
“…The cytosolic enzyme α‐ketoisocaproate dioxygenase (or 4‐hydroxyphenylpyruvate dioxygenase)48 produces HMB from L‐Leu. KICD is mainly expressed in the liver, kidney, and neurons, but it is absent in muscle tissues,49 although in a recent study,41 this enzyme has been shown to be expressed in skeletal muscle at low levels. This enzyme provides a direct pathway for the synthesis of HMB, and this pathway accounts for up to 5% of the L‐Leu catabolism in humans 23…”
Section: Discussionmentioning
confidence: 96%
“…HMB has positive effects promoting strength and lean body mass in sport performance 40. Also, as a therapeutic supplement (especially in atrophic conditions), HMB stimulates muscle protein synthesis and reduces protein degradation 9, 17, 18, 21, 41. The increase in protein synthesis by HMB has been correlated with the activation of mTOR and two of its substrates 4E‐BP1 and S6K1, proteins involved in the translation of mRNA and protein synthesis 14, 40…”
Section: Discussionmentioning
confidence: 99%